INTERCONNECTIONS STRUCTURE OF RETINA FUNCTIONAL CONDITION INDEXES DURING COMPLICATED FORM OF MYOPIA - Lapkina, I.I. (World of Medicine and Biology, 2013)
The results of interconnections dynamics evaluation of structural-functional condition indexes of retina during the treatment of different stages of complicated myopia are provided. It has been shown, that original connections structure in the indexes system of retina functional condition during different stages of complicated myopia is similar, and that points at single pathogenetic base of disease. As a result of traditional therapy amelioration of researched system appears only at the first stage of complicated myopia, as reflected by the increase of number of factors and decrease of number of meaningful connections between them. Significant number of meaningful connections in factor structure after traditional treatment during the second stage of myopia points at low effectiveness of carried out treatment. Factor structure during the third degree of myopia is evidence of ineffectiveness of carried out treatment that is proved by the preservation of initial configuration of connections and significant determinateness of researched system of indexes.